2017
DOI: 10.1103/physrevd.96.084013
|View full text |Cite
|
Sign up to set email alerts
|

Massless charged particles: Cosmic censorship, and the third law of black hole mechanics

Abstract: The formulation of the laws of black hole mechanics assumes the stability of black holes under perturbations in accordance with the "cosmic censorship hypothesis"(CCH). CCH prohibits the formation of a naked singularity by a physical process from a regular black hole solution with an event horizon. Earlier studies show that naked singularities can indeed be formed leading to the violation of CCH if a near-extremal black hole is injected with massive charged particles and the back reaction effects are neglected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…where ω is the energy of the ingoing fermion. Substituting equation (30) into equations (26), (27) and canceling A and B, we get…”
Section: Fermion Absorptionmentioning
confidence: 99%
“…where ω is the energy of the ingoing fermion. Substituting equation (30) into equations (26), (27) and canceling A and B, we get…”
Section: Fermion Absorptionmentioning
confidence: 99%
“…Overcharging via test field absorption instead of test particle was pursued in [9][10][11]. Various other attempts of overcharging have been carried out in last few decades over a wide range of black hole solutions in general relativity in order to look for any possible violation of cosmic censorship [12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the physics of general relativity prohibits such a process, the test particles with sufficient charge and angular momentum, which can overcharge the black hole get repelled and does not enter the event horizon. Similar analysis has been done on various scenarios, and it is always found that the formation of a naked singularity by overcharging is not possible [12][13][14][15][16][17][18][19][20][21]. On the other hand, Hubeny has shown that if the initial configuration is near extremal, it is possible to overcharge a Reissner-Nordstrom (RN) black hole using test particle absorption [22].…”
Section: Introductionmentioning
confidence: 66%
“…This is first attempted in the seminal work of Wald [6], and he proved that it is impossible to overcharge or overspin an extremal Kerr-Newman black hole via the process of test particle absorption. In followup works, the validity of WCC for several class of black hole spacetimes has been extensively studied [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Also, Hubeny showed that it is possible to overcharge a near extremal black hole to create a naked singularity in the final state via charged particle absorption as long as back-reaction effects can be neglected [24].…”
Section: Introductionmentioning
confidence: 99%